SAZHINITE-(LA), NA3LASI6O15 (H2O)2, A NEW MINERAL FROM THE ARIS PHONOLITE, NAMIBIA: DESCRIPTION AND CRYSTAL STRUCTURE - Cámara F.; Ottolini L.; Devouard B.; Garvie L.A.J.; Hawthorne F.C. (My University, 2006)
Sazhinite-(La) is a new mineral from the Axis phonolite, Windhoek, Namibia. It occurs in vesicles within the phonolite, together with other species crystallized from late-stage hydrothermal fluids: natrolite, aegirine, microcline, apophyllite, sphalerite, analcime, fluorite, villiaumite hydroxylapatite, galena, makatite, quartz, eudialyte, kanemite, tuperssuatsiaite and korobitsynite. Sazhinite-(La) forms small euhedral crystals up to 1 mm long and 0.4 mm wide, elongated along [001] and flattened on (010), exhibiting the forms {h01}, {100} and {001}. It has good cleavage parallel to {010} and {001}. Twinning was not observed. Crystals are brittle with a Mohs hardness of 3, creamy white with a white streak, vitreous to pearly lustre, and translucent to transparent. In plane-polarized light, crystals are colourless with a = Z, b = Y, c = X. It is biaxial positive with α = 1.524, β = 1.528, γ = 1.544, all ±0.002, 2VZ(obs) = 46(1)°, and 2VZ(calc.) = 53.6°. Sazhinite-(La) is orthorhombic Pmm2, a = 7.415(2), b = 15.515(3), c = 7.164(1) Å, and V = 824.2 Å3. One crystal was studied by X-ray diffraction, electron microprobe and secondary ion mass spectrometry (SIMS) microanalysis, leading to the average composition (Na2.87K0.02Sr0.001)∑2.90 [La0.41Ce0.35Pr0.02Nd0.04 (Sm,Gd,Dy,Er,Yb)∑0.01,Th0.09U0.01 Y0.01Zr0.01Ca0.08Li0.01] ∑1.044T(Si5.87Si0.06 B0.01) (O14.86F0.14)· (H2O)2. Weighted full-matrix least-squares refinement on 3369 reflections yielded Rall = 3.8%. The structure is built of corrugated [Si6O15]6- layers linked by [7]-coordinated REE and R4+ cations. This framework leaves channels that contain three [5]- and [6]-coordinated Na cations per formula unit that compensate for the residual charge on the silicate layers. The SIMS analyses confirm a Na content of 3 atoms per formula unit, leading to an ideal formula of Na3LaSi6O15(H2O)2. The third Na atom is bonded to H2O groups and therefore the total content of both Na and H2O may be reduced to 2 and 1 per formula, respectively. The depletion in Na allows for the entrance of high-charge cations such as Th4+. © 2006 The Mineralogical Society.
Keywords: EMPA; NEW MINERAL; RARE-EARTH MINERALS; SAZHINITE-(LA); SCXRD; SIMS